2011
DOI: 10.4194/trjfas.2011.0110
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Lipid, moisture, fatty acid, and mineral contents of gold band goatfish (Upeneus moluccensis) (Bleeker, 1855) and striped red mullet (Mullus surmuletus) (Linnaeus, 1758) were investigated. The lipid and moisture contents in the two species were found to be significantly different from each other (P<0.05). Lipids of striped red mullet include significantly (P<0.05) higher levels of C14:0, C15:0, C16:1, C17:1, C18:1n9, C18:2n6, C20:3n6, DHA (Docosahexaenoic Acid, C22:6n3) and EPA (Eicasapentaenoic Acid, C20:5n3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…Overall, potassium was found to be the mineral with the highest concentration in all the fleshy tissues compared to other minerals analyzed. The mean potassium values obtained in this study are comparable to potassium values of 1276.4mg/kg and 2064.8mg/kg reported by Oksuz et al (2011) for gold band goatfish and stripped red mullet respectively. The potassium values obtained in this study are also comparable to the studies of Mohammed et al (2010) and Luczyiska et al (2009) who reported mean potassium concentrations ranges of 954-1210mg and 1429-2387mg in species of freshwater fish in Sudan and Poland respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, potassium was found to be the mineral with the highest concentration in all the fleshy tissues compared to other minerals analyzed. The mean potassium values obtained in this study are comparable to potassium values of 1276.4mg/kg and 2064.8mg/kg reported by Oksuz et al (2011) for gold band goatfish and stripped red mullet respectively. The potassium values obtained in this study are also comparable to the studies of Mohammed et al (2010) and Luczyiska et al (2009) who reported mean potassium concentrations ranges of 954-1210mg and 1429-2387mg in species of freshwater fish in Sudan and Poland respectively.…”
Section: Discussionsupporting
confidence: 85%
“…45 Taurine supplementation has been found to increase adiponectin levels, Table 4, eight minerals were quantied in S. zunasi Bleeker, including four macro minerals (Ca, K, Na, and Mg) and four trace minerals (Fe, Zn, Mn, and Cu). Ca (1240 AE 0.02 mg/100 g) was the major mineral in S. zunasi Bleeker, the content of which was found to be higher than that in Sardinella longiceps (523.9 AE 45.6 mg/100 g), 47 Mullus surmeletus (398.6 AE 105.9 mg kg À1 ) and Upeneus moluccensis (617.4 AE 90.5 mg kg À1 ), 48 followed by K (308 AE 0.08 mg/100 g), Na (168 AE 0.04 mg/100 g) and Mg (56.30 AE 2.7 mg/ 100 g). Ca rich in S. zunasi Bleeker suggests that it could be a good choice for nutritional supplements.…”
Section: Proximate Compositionmentioning
confidence: 88%
“…Ca rich in S. zunasi Bleeker suggests that it could be a good choice for nutritional supplements. The analysis of microelements revealed that S. zunasi Bleeker possessed Fe (9.48 AE 0.05 mg/100 g), Zn (2.55 AE 0.06 mg/100 g) and Mn (0.59 AE 0.01 mg/100 g), and the content of Cu was less than 0.5 mg/ 100 g. Fe is one of the essential trace minerals that good for health, the level of Fe (9.48 AE 0.05 mg/100 g) in S. zunasi Bleeker was much higher than that in Upeneus moluccensis (7.3 mg kg À1 ) and Mullus surmeletus (6.4 mg kg À1 ), 48 indicated S. zunasi Bleeker may be taken as a good supplement source of Fe with healthy benets to human. 49…”
Section: Proximate Compositionmentioning
confidence: 92%
“…Polat et al [32] reported that seasonal lipid level of red mullet was in the range of 3.68-5.76% using Bligh and Dyer method. The lipid contents of gold band goatfish and red mullet were found to be 4.35 AE 1.05 and 10.38 AE 1.9%, respectively, by Oksuz et al [33] with Bligh and Dyer method. Total lipid levels of red mullet were reported to be highly variable, with very low levels in spring (0.96-1.48%) and high levels in autumn (7.28-8.72%) by Di Lena et al [34] using Bligh and Dyer method.…”
Section: Lipid Contentmentioning
confidence: 94%
“…[33,34,37,[39][40][41] Those fatty acids occurring in the highest amounts were myristic acid (C14:0, 2.32 AE 0.12 mg 100 g À1 for Soxhlet to 184.62 AE 3.47 mg 100 g À1 for Bligh and Dyer), palmitic acid (C16:0, 17.78 AE 0.16 mg 100 g À1 for Soxhlet to 1164.70 AE 9.64 mg 100 g À1 for Bligh and Dyer), palmitoleic acid (C16:1, 3.37 AE 0.05 mg 100 g À1 for Soxhlet to 378.78 AE 3.47 mg 100 g À1 for Bligh and Dyer), stearic acid (C18:0, 6.95 AE 0.24 mg 100 g À1 for Soxhlet to 334.06 AE 1.93 mg 100 g À1 for Bligh and Dyer), oleic acid (C18:1n-9, 7.54 AE 0.61 mg 100 g À1 for Soxhlet to 1638.9 AE 4.45 mg 100 g À1 for Bligh and Dyer), cis-vaccenic acid (18:1n-7, 2.11 AE 0.04 mg 100 g À1 for Soxhlet to 269.43 AE 0.77 mg 100 g À1 for Bligh and Dyer), linoleic acid (C18:2n-6, 0.88 AE 0.10 mg 100 g À1 for Soxhlet to 58.63 AE 2.70 mg 100 g À1 for Bligh and Dyer), erucic acid (C22:1n9, 1.29 AE 0.09 mg 100 g À1 for Soxhlet to 125.11 AE 4.24 mg 100 g À1 for UAE), eicosapentaenoic acid (EPA, C20: 5n3, 2.05 AE 0.29 mg 100 g À1 for Soxhlet to 278.15 AE 3.09 mg 100 g À1 for Bligh and Dyer), decosahexaenoic acid (DHA, C22: 6n3, 10.82 AE 0.38 mg 100 g À1 for Soxhlet to 454.06 AE 11.48 mg 100 g À1 for UAE). These results are in agreement with previous studies on fatty acid profiles of European eel extracted from Bligh and Dyer, [31,42] from Folch method, [43] brushtooth lizardfish from Bigh and Dyer, [38] red mullet from Bligh and Dyer, [32,34,38,39,44] striped redmullet (or surmullet) from Bligh and Dyer, [33] striped redmullet from Folch method, [37] common pandora extracted from Bligh and Dyer method, [45] from Folch method, [46] from Soxhlet method, [39] brushtooth lizardfish from Bligh and Dyer, [17,41] and goldband goatfish from Bligh and Dyer, [33] extracted according to Lovell [36] method. [35] Like lipid content, the fatty acid composition of fish species is not constant and it varies depending on many ecological and morphological factors such as species, season, location, diet, lifestage, and age of the fish, which have major www.advancedsciencenews.com www.ejlst.com impacts on the nutrient levels of fish and even vary broadly within species and between species [47] Previous report...…”
Section: Fatty Acid Compositionmentioning
confidence: 99%